Results of combined radiotherapy and hormonal treatment of prostate cancer patients with initial PSA value >40 ng/ml - Kubeš, Jiri; Jakub, Cvek; Vladimir, Vondráček; Jan, Dvořák; Sona, Argalacsová; Matej, Navrátil; Jan, Buřil (Reports of practical oncology and radiotherapy, 2012)
AIM: To evaluate the outcome of prostate cancer patients with initial PSA value >40 ng/ml. BACKGROUND: The outcome of prostate cancer patients with very high initial PSA value is not known and patients are frequently treated with palliative intent. We analyzed the outcome of radical combined hormonal treatment and radiotherapy in prostate cancer patients with initial PSA value >40 ng/ml. METHODS: Between January 2003 and December 2007 we treated, with curative intent, 56 patients with non-metastatic prostate cancer and initial PSA value >40 ng/ml. The treatment consisted of two months of neoadjuvant hormonal treatment (LHRH analog), radical radiotherapy (68-78 Gy, conformal technique) and an optional two-year adjuvant hormonal treatment. RESULTS: The median time of follow up was 61 months. 5-Year overall survival was 90%. 5-Year biochemical disease free survival was 62%. T stage, Gleason score, PSA value, and radiotherapy dose did not significantly influence the outcome. Late genitourinal and gastrointestinal toxicity was acceptable. CONCLUSION: Radical treatment in combination with hormonal treatment and radiotherapy can be recommended for this subgroup of prostate cancer patients with good performance status and life expectancy.
Keywords: High risk; Prostate cancer; Radiotherapy; PSA